PERSOALAN KEHIDUPAN KONTEMPORER: MENGGAGAS KAJIAN SACHEDINA TENTANG THEOLOGI PLURALISME - Dodi, Limas (EMPIRISMA: JURNAL PEMIKIRAN DAN KEBUDAYAAN ISLAM, 2017)
According to Abdulaziz Sachedina, the main argument of religious pluralism in the QurÃ¢â‚¬â„¢an based on the relationship between private belief (personal) and public projection of Islam in society. By regarding to private faith, the QurÃ¢â‚¬â„¢an being noninterventionist (for example, all forms of human authority should not be disturb the inner beliefs of individuals). While the public projection of faith, the QurÃ¢â‚¬â„¢an attitude based on the principle of coexistence. There is the willingness of the dominant race provide the freedom for people of other faiths with their own rules. Rules could shape how to run their affairs and to live side by side with the Muslims. Thus, based on the principle that the people of Indonesia are Muslim majority, it should be a mirror of a societieÃ¢â‚¬â„¢s recognizion, respects and execution of religious pluralism. Abdul Aziz Sachedina called for Muslims to rediscover the moral concerns of public Islam in peace. The call for peace seemed to indicate that the existence of increasingly weakened in the religious sense of the Muslims and hence need to be reaffi rmed. Sachedina also like to emphasize that the position of peace in Islam is parallel with a variety of other doctrines, such as: prayer, fasting, pilgrimage and so on. Sachedina also tried to show the argument that the common view among religious groups is only one religion and traditions of other false and worthless. Ã¢â‚¬Å“AntipluralistÃ¢â‚¬Â argument comes amid the reality of human religious differences. Keywords: Theology, Pluralism, Abdulaziz Sachedina